RAISING AWARENESS ABOUT THE COVID-19 HEALTH PROTOCOL TO THE PUBLIC WHEN CARRYING OUT ROUTINE ACTIVITIES IN THE PANDEMIC PERIOD - Firdaussa, Tasya Shiffa; Anjani, Veronica; Fitri, Teza Nur; Anggela, Ratih Febi; Kusuma, Jaka Wijaya (Nindikayla Institute, 2024)
The initial stage conducted by community service students’ group 26 is to follow the routine activities of the community, then tuck into socialization about the importance of public awareness of health protocols in routine daily activities in the pandemic period. Community Service group 26 follows community study activities by always obeying health protocols. The study activity begins with the reading of sholawat by mothers - mothers of study. However, students of community service group 26 always directed the community to keep their distance and use hand sanitizer. Community service group 26 also provides socialization about health protocols to the banana horn farming group of prosperous sari blooms. So that they are aware of the importance of health protocols when doing activities outside the home.